“People in my life just play different roles”: A retrospective qualitative study of friendships among young adults who self-harmed during adolescence - Delfina Bilello; Ellen Townsend; Matthew R. Broome; Stephanie Burnett Heyes (PLoS ONE, 2025)
Self-harm is a global public health concern presenting increasing rates in recent years, especially among young people. This population seldom access formal help, and typically rely on informal sources of support, mainly friends. The role, importance and meaning of friendships in the context of self-harm remains poorly understood, highlighting the need to explore young people’s lived experiences. In the present study we conducted semi-structured retrospective qualitative interviews, prompted by the Card-sort Task for Self-Harm About Friends (CaTS-AF), to explore the experiences of 11 young adults (M=19.09; SD=0.70; M=2, F=9) who self-harmed during adolescence. Data were analysed using Reflexive Thematic Analysis (RTA). Three themes were developed which consider 1) the role of friendships in self-harm progression; 2) the role of self-harm in friendship evolution; and 3) the meaning of friendships in the context of adolescents’ self-harm. The first two themes highlight the interdependent nature of friendships and self-harm, where these two experiences influence one another. Furthermore, not only are friendships shaped by self-harm, but they acquire specific meanings, dynamics and expectations within the context of the behaviour. Overall, friends are a key part of adolescents’ self-harm, as sources of both risk and protection. It is essential to further integrate friendships, a developmentally significant aspect of adolescents’ social experiences, into self-harm research and clinical practice.